Feasibility Study to Connect All African Higher Education Institutions to High-Speed Internet : Mozambique Case Study - World Bank; Knowledge Consulting Ltd. (World Bank, Washington, DC, 2021)
Following the Introduction in chapter one, the report provides a country overview in chapter two to provide the national context. The connectivity gap has both a supply-side and a demand-side: Chapter three explores the demand-side, focusing on ICT in the education sector and the challenges impacting the use of information and communication technologies for teaching, learning, and research, creating the pull factors; and chapter four examines the supply-side, the ICT sector's key components and the challenges affecting high-speed connectivity. The National Research and Education Network (NREN), the Mozambique Research and Education Network (MoRENet) is the higher education response created to close the gap between the demand-side and the supply-side, and chapter five presents a high-level summary of the status of this NREN as well as its achievements and limitation in delivering high-speed connectivity to HEIs. Drawing on findings from the earlier chapters, chapter six discusses the cost of connecting all higher education institutions in Mozambique to high-speed Internet. The conclusion is given in chapter seven followed by appendices.